Cloning, Expression And Characterization Of Ahlinactivating aiiA Gene Homologue In Escherichia coli - Subashini, Muniandy (2014)

(untitled)
Cell-to-cell communication pathway of single-celled microbes is usually coordinated by quorum sensing (QS) system mediated by signal molecules. This cell density-dependent system plays a vital role in functional coordination of most pathogenic bacteria. Laluan komunikasi antara sel-sel mikrob bersel tunggal biasanya diselaraskan oleh penderiaan kuorum yang dikoordinasikan oleh molekul isyarat. Sistem ini bergantung kepada kepadatan sel dan memainkan peranan penting dalam penyelarasan and pengekspresan gen kebanyakan bakteria patogenik.